2011
DOI: 10.1016/j.jpha.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of chlorogenic acid after oral administration in rats

Abstract: The present study was aimed at the comparison of the pharmacokinetics of pure chlorogenic acid and extract of Solanum lyratum Thunb. The animals were allocated to two groups, and were administered chlorogenic acid or extract of S. lyratum Thunb. at a dose of 50.0 mg/kg orally. Blood samples were collected up to 8 h post-dosing. Plasma chlorogenic acid analyses were performed using an HPLC method with UV detector. The pharmacokinetic parameters were evaluated using non-compartmental assessment. Significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Product A, B, C, D, E, F extracts were dissolved in saline to give the concentration of 50% (v/v) immediately prior to drug administration. The contents of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 3,5-dicaffeoylquinic acid and 3,4dicaffeoylquinic acid in product extracts respectively were 16 This validated method was applied to monitor the plasma concentrations of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 3,5-dicaffeoylquinic acid and 3,4-dicaffeoylquinic acid simultaneously following single oral administration of Flos Lonicerae preparations in rats.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Product A, B, C, D, E, F extracts were dissolved in saline to give the concentration of 50% (v/v) immediately prior to drug administration. The contents of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 3,5-dicaffeoylquinic acid and 3,4dicaffeoylquinic acid in product extracts respectively were 16 This validated method was applied to monitor the plasma concentrations of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 3,5-dicaffeoylquinic acid and 3,4-dicaffeoylquinic acid simultaneously following single oral administration of Flos Lonicerae preparations in rats.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…There were several articles concerning the quantification of chlorogenic acid in plasma [9][10][11][12][13][14][15][16][17]. However, apart from chlorogenic acid, simultaneous pharmacokinetic studies of other phenolic acids have not been reported after oral administration of Flos Lonicerae preparations in rats, and very little attention has been devoted to the pharmacokinetic studies of these components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protection is thought to be mediated via inhibiting down-regulation of anti-apoptotic proteins Bcl-2 and Bcl-X(L) and cleavage of caspase-3 and pro-poly (ADP-ribose) polymerase and additionally up regulation of the anti-oxidant enzyme NADPH quinine oxidoreductase 1 NQO1 [21][22][23] . Although characterization of chlorogenic acid and its metabolites is still an ongoing area of study, researchers found a plasma half-life of ~1.7 hours for chlorogenic acid in rats after oral administration 24 .…”
Section: Chlorogenic Acids (Cga)mentioning
confidence: 99%
“…Due to multiple viral species and serotype, antigenic variation, and genomic mutations, there is no proven effective treatment for EV71 infection [11]. CHA is the major active ingredient found in many traditional Chinese herbs and herbal medicine [12]. Structurally, CHA is an ester formed between caffeic acid and L-quinic acid.…”
Section: Introductionmentioning
confidence: 99%